2017
DOI: 10.4067/s0718-95162017005000010
|View full text |Cite
|
Sign up to set email alerts
|

Native microorganisms as potent bioinoculants for plant growth promotion in shifting agriculture (Jhum) systems

Abstract: Microorganisms native to shifting cultivation were isolated and screened for plant growth promotion (PGP) properties. The bacterial and fungal isolates that exhibed production of indole compounds, siderophores, and ammonia; phosphate solubilization; and catalase activity, were selected and tested for their ability to promote the early growth of upland rice plants. Potential isolates from a preliminary seed germination assay carried out in plates were further tested in pots under greenhouse conditions. Observat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 25 publications
(26 reference statements)
1
23
0
Order By: Relevance
“…They serve as vehicles for the transport into microbial cells of ferric ion which is otherwise unavailable. The production of siderophores by Trichoderma candidates for plant disease control and growth promoting offers the possibilities to replace chemical pesticides [53,54]. In this regard, fungal Trichoderma isolates were investigated by qualitative test on King's B medium supplemented with 8-hydroxyquinoline ( Figure 4a).…”
Section: Discussionmentioning
confidence: 99%
“…They serve as vehicles for the transport into microbial cells of ferric ion which is otherwise unavailable. The production of siderophores by Trichoderma candidates for plant disease control and growth promoting offers the possibilities to replace chemical pesticides [53,54]. In this regard, fungal Trichoderma isolates were investigated by qualitative test on King's B medium supplemented with 8-hydroxyquinoline ( Figure 4a).…”
Section: Discussionmentioning
confidence: 99%
“…The improved growth, nutrient absorption, and physiology of rice in response to PGPR inoculation at each irrigation interval and in saline soil could be ascribed to the biosynthesis of phytohormones such as IAA. IAA may be related to the total biomass of the plant [52] and augmented availability of nutrients [53]. It may also influence the production of ACC deaminase, EPS, and osmolytes [54,55].…”
Section: Soil Physicochemical Propertiesmentioning
confidence: 99%
“…(2009) when inoculating strains of Azospirillum and Pseudomonas in wheat; and by Banerjee et al (2017), who conducted a study in rice and indicated that the increase in shoot and root biomass resulting from the inoculation with these microorganisms has beneficial effects on crop and soil quality.…”
Section: Discussionmentioning
confidence: 99%